Black hole thermodynamics in the presence of a maximal length and minimum measurable in momentum. (8th November 2021) - Hamil, B.; Lütfüoğlu, B. C.
Abstract: In this work, incorporating the effect of the minimum measurable in momentum and maximal length, we studied the thermodynamics property of the Schwarzschild black hole and the Unruh effect. According to this scenario, we see that the black hole temperature cannot be smaller than a certain minimum value . Moreover, we find that black hole mass cannot be larger than a maximum mass value . Considering these findings first we compute the corrected Hawking temperature vs. the mass and examine its characteristic behavior. Then, we derive the black hole's entropy and heat capacity. We find that the black hole is stable when . Finally, we examined the modified Unruh effect. We find that the modified Unruh temperature explicitly depends on α .